Introduction to paint chemistry and principles of paint technology - Turner, G. P. A. (Gerald Patrick Anthony) (Chapman & Hall, 1998)
This work provides a comprehensive introduction to paint technology supported by the relevant aspects of chemistry and physics. It covers the basic science and is devoted to paint composition, formulation and drying mechanisms, paint ingredients such as solvents, pigments and additives, and the different paint groups by chemical type. Throughout the book the authors emphasize the factors which govern the choice of a particular paint for a particular job. This new edition has been thoroughly revised to modernize and clarify the text. Areas of new development have been added including environmental impacts, safety issues and modern paint making techniques. Nomenclature and units have also been updated and a glossary of technical terms added. This book should be of interest as a course text for paint technology students and technical staff concerned with the paint industry.